ANTIBACTERIAL ACTIVITY OF FRACTIONATED SANDALWOOD OILS - A. T. Karossi; H. Agustina; L. Sutedja (Jurnal Kimia Terapan Indonesia, 1993)
Sandalwood oil was prepared through water distillation of sandalwood (Sansalum album L) sawdust. The inhibitory activity of the oil was tested against Staphylococcus aureus and Bacillus cereus. This antibacterial active oil was further fractionated through column chromatography into five fractions. Larger antibacterial activity, expressed as inhibitory diameter ( ID ), was observed in the prepared sandalwood oil and its fractions compared to sandalwood oil originated from Kupang and sanialol from International Flavors and Fragrance ( IFF ). The inhibitory diameter of the isolated sandalwood oil against S. aureus and B. cereus were 8.75 and 8.20 mm respectively. While the IV of sandalwood oil from Kupang and santalol IFF against S aureus were 7.20 and 7.23 mm, and against B. cereus 6.62 and 7.35 mm respectively. The ID of the sandalwood oil fractions against S aureus ranged between 7.32 - 9.93 mm, and the largest inhibition was shown by fraction -2. Against Bicereus the IV ranged between 7.64 - 11.12 mm., and the largest inhibition was shown by fraction - 1. Suggested possible structures for sandalwood oil fractions were based on the infra red spectra of the oils and sandalwood oil components.